2003
DOI: 10.1016/s0927-0256(03)00054-5
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of the performances of the bonded composite patch for reducing stress concentration and repairing cracks at notch

Abstract: In this paper, the finite element analysis is applied to study the performance of the bonded composite reinforcement or repair for reducing stress concentration at a semi-circular lateral notch and repairing cracks emanating from this kind of notch. The effects of the adhesive properties on the variation of the stress intensity factor at the crack tip were highlighted. The obtained results show that the stress concentration factor at the notch tip is reduced about 30% and the maximal reduction of the stress in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 14 publications
(11 reference statements)
0
22
0
Order By: Relevance
“…The stress intensity factor is then reduced by the presence of the patch. Several authors showed that the mode I stress intensity factor of repaired crack, exhibits an asymptotic behaviour as the crack length increases [1][2][3][4][5]. The asymptotic value of the SIF was approximated by Rose [6] by the formulas:…”
Section: Introductionmentioning
confidence: 99%
“…The stress intensity factor is then reduced by the presence of the patch. Several authors showed that the mode I stress intensity factor of repaired crack, exhibits an asymptotic behaviour as the crack length increases [1][2][3][4][5]. The asymptotic value of the SIF was approximated by Rose [6] by the formulas:…”
Section: Introductionmentioning
confidence: 99%
“…This means that, for repaired cracks, the stress intensity factor becomes independent of the crack length, which facilitate the control of the crack growth. Several authors [16,17,19,24] observed this asymptotic behavior of the stress intensity factor for repaired cracks. The stress intensity factor follows an ascending curve for small cracks, reaches a maxima then decreases and stabilizes towards an asymptotic value.…”
Section: Resultsmentioning
confidence: 62%
“…The development of this technology has been accelerated by many studies in the aerospace industry in the interests of increasing the service life and reducing the repair cost [4][5][6][7]. A well-designed and bonded patch causes the stress intensity at the crack tip to reach an asymptotic value K 1 [8][9][10][11]. It means that the stress intensity factor at the crack tip becomes independent of the crack length.…”
Section: Introductionmentioning
confidence: 99%